(3caGAI GdPGcQI GdYGedI ai YdGbJgG HGdJacjQ GdJLQjOi GdELJeGYi dOi HYV GdJdGejP GdeQGgbjf GdchjJjjf ef Phi GdGMJjGLGJ GdNGUI h GdCShjGA (B= s The efficacy of working memory and its relation with social abstract thinking among samples of Kuwaiti special needs adolescents and normal students - (3MfGf YHOGddWja aQMGf GdOhNjs; (3eMeO fLjH CMeO GdUHhI (B: s ((3GdbGgQI (B: s (3MfGf YHOGddWja aQMGf GdOhNj (B: s, 2012)
(3gOaJ GdOQGSI GdQGgfI Edi JYQa MLe GdYdGbI GdGQJHGWjI h hLgJgG Hjf cd ef GdPGcQI GdYGedI h GdJacjQ GdJLQjOj GdGLJeGYj h GdJUhQj(B: (3h eG EPG cGfJ Jdc GdYdGbI eQJHWI HfhY GdYjfI (B( (3GdCShjGA(B: (3h Phj GdGMJjGLGJ GdNGUI (B): (3h GdLfS (B( (3PchQ(B: (3h EfGK (B): (3HGdEVGaI Edi OQGSI GdaQhb Hjf GdCShjGA h Phj GdGMJjGLGJ GdNGUI aj GdPGcQI GdYGedI (B((3Hcd echfGJgG(B: (3GdUhJj(B-(3GddaXj(B: (3h GdHUQj(B-(3GdecGfj(B: (3h Gdechf GdJfajPj GdeQcRj (B) (3h GdJacjQ GdJLQjOj GdGLJeGYj h GdJUhQj(B: (3cPdc eMGhdI GdJejjR Hjf cd aFI ef GdaFGJ GdNGUI HfGA Ydi caGAI COGFge Ydi cd echf ef echfGJ GdPGcQI GdYGedI h GdJacjQ GdJLQjOj GdGLJeGYj h GdJUhQjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe Yde GdfaSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJacjQ GdJLQjOi GdELJeGYis; (3Phi GdGMJjGLGJ GdNGUIs; (3caGAI GdPGcQI GdYGedIs